Les Technologies De L Information Et De La Communication (TIC) Promeuvent-Elles L Inclusion Financiere En Afrique Sub-Saharienne ? Do Information And Communication Technologies (ICTs) Promote Financial Inclusion In Sub-Saharan Africa? (Global Journal of Human-Social Science, 2020)
Abstract not found
Keywords: ICT; financial inclusion; theory of the diffusion of innovation